Kontrolbegrebets betydning for kausativalternationen i spansk: En kognitiv-typologisk analyse - Henriette Balieu (Copenhagen Business School (CBS), 2009)
– The dissertation seeks to answer the following questions: Which semantic properties allow for a verb to appear as well transitively as intransitively without any morphological changes, i.e. a semantic characterization of the verbs that alternate. When does the reflexive pronoun se appear in the intransitive version of the alternation? What characterizes the situations referred to by the alternation and what makes them so apt to appear in the causative alternation not only in Spanish but also in typologically related and unrelated languages, i.e. a more general characterization/description of the situations referred to by the verbs in the alternation.
hdl:10398/7945
Keywords: 650